2007
DOI: 10.1111/j.1464-5491.2007.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in diabetic retinopathy

Abstract: These data demonstrate that moderate or more severe retinopathy is more common in Polynesians than Europeans. The reasons for this are unclear, but may be related to long-standing hyperglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
0
40
2
Order By: Relevance
“…Fifty-seven studies published from 1990 to 2008 met the inclusion criteria: 13 European studies on AMD (4 multicentre studies [13,[22][23][24] , 6 prevalence studies from the Netherlands [25] , Germany [26] , France [27] , the UK [28] , the European North of Russia [29] and Bulgaria [2] , and 3 incidence studies from Rotterdam [22,30] and Germany [31] ), 23 studies of diabetic retinopathy (1 global [32] , 3 European [33][34][35] ; 2 multicentre European [15,36,37] and 2 multicentre from Spain [38] and Germany [26,39] , 1 long-term follow-up study from Germany [40] ; 7 population-based studies [2,30,31,[41][42][43][44][45] , 5 cross-sectional studies from Germany [39] , France [46] , Europe [27,37] , Spain [47] and 2 literature reviews [16,35] ), 5 studies of ocular hypertension, including 4 cross-sectional studies: 1 from Spain [48] , 2 from France [49,50] , 1 cross-sectional study of high intraocular pressure ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-seven studies published from 1990 to 2008 met the inclusion criteria: 13 European studies on AMD (4 multicentre studies [13,[22][23][24] , 6 prevalence studies from the Netherlands [25] , Germany [26] , France [27] , the UK [28] , the European North of Russia [29] and Bulgaria [2] , and 3 incidence studies from Rotterdam [22,30] and Germany [31] ), 23 studies of diabetic retinopathy (1 global [32] , 3 European [33][34][35] ; 2 multicentre European [15,36,37] and 2 multicentre from Spain [38] and Germany [26,39] , 1 long-term follow-up study from Germany [40] ; 7 population-based studies [2,30,31,[41][42][43][44][45] , 5 cross-sectional studies from Germany [39] , France [46] , Europe [27,37] , Spain [47] and 2 literature reviews [16,35] ), 5 studies of ocular hypertension, including 4 cross-sectional studies: 1 from Spain [48] , 2 from France [49,50] , 1 cross-sectional study of high intraocular pressure ...…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature reviewed in this study, diabetic retinopathy affects 3 [32] to 4.1% [33] of Europeans. Recent epidemiological studies have shown that France [46] and Germany [39] show the highest prevalence of diabetic retinopathy in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maori were over-represented in patients with retinopathy and maculopathy, but under-represented within the screening population [16]. In New Zealand, moderate or more severe retinopathy is more common in Polynesians than Europeans [17].…”
Section: Diabetic Complications In Indigenous People: Nephropathy and Rmentioning
confidence: 99%
“…It accounts for about 2.4 million cases of blindness globally (4). A proportion of 4.8% of the global population suffers from DR (5), while 3 (5) to 4.1% (6) of Europeans are affected.…”
Section: Introductionmentioning
confidence: 99%